Comparative studies of the mountain Kinnekulle vegetation - Marina Voinova; Benny Lönn (Academia Biology)
In the present paper, we report the results of environmental monitoring of the mountain Kinnekulle habitat area (Västra Götaland county, Sweden) and discuss its nature conservation value. As part of our comparative study of Kinnekulle’s flora, between 2018 and 2023 we have studied population dynamics of plants growing there. In the present study, we compare our plant inventory results and those provided by Carl Linnaeus in his book “Västgöta Resa År 1746” (“The trip to Västra Götaland, 1746”), providing evidence that most of the plants listed by Linnaeus can still be found in the Kinnekulle area (58–94% occurrence). A part of the paper is a historical tribute to Carl Linnaeus and his trip to the Kinnekulle area. An English translation of Linnaeus’ text on Kinnekulle’s nature and plant inventory list can be found in the supplement materials of the paper.